The challenge to Mahmoud Abu Rayyah's thoughts on the significance of Abu Hurairah and Ka'b Al-Ahbār in hadīth narration - Badi, Jamal Ahmed Bashier; Gasmelsid, Saadeldin Mansour; Nasution, Alhafidh (USIM Press, 2024)
In response to Mahmoud Abu Rayyah's accusations against Ka'b al-Ahbār, this study attempts to address the claims that he was the ‘first Jewish’ in Islam, that deceit and hypocrisy led to his conversion to Islam, and that he was the first to support the Jewish people's movement in Jerusalem. This study uses qualitative methods with a type of literature analysis supplemented by analysis of content to analyze to understand Abu Rayyah's thoughts on his criticism of the relationship between Abu Hurairah and Ka'b al-ahbar. In this case the author also analyzes the criticism with the method of criticism of Abu Rayyah's thoughts. In response, the following was said: Regarding the Islamic conversion of al-Ahbār: There is universal agreement among historians regarding the validity of al-Ahbār’s conversion to Islam, having previously served as a Jewish priest. Ka'b was among the wisest Jews in his generation. He addressed Arabic with ease and had extensive knowledge of both the Prophet's Sunnah and the Holy Qur'an. As a result, Ka’b al-Ahbār 's conversion to Islam helped Muslims gain a thorough understanding of Judaism and played a significant role in converting Jews to Islam. Considering the connection between Abu Hurairah and Ka'b al-Ahbār, all historians concur that Abu Hurairah used to obtain numerous hadiths from al-Ahbār, who was one of his narrators. The Israeli hadiths and their attribution to the Prophet, peace and blessings be upon him, were not transmitted to Abu Hurairah by al-Ahbār, albeit these claims are unsupported. The hadiths from Ka'b al-Ahbār were verified by other sources, according to evidence that Abu Hurairah once collected. On the authority of the Prophet, regarding the hadiths recounted by Abu Hurairah.